Asociación diámetro-altura total en plantas Iryanthera juruensis Warb.” cumala colorada” y Guarea macrophylla M. Vahl "requia blanca" en diferentes tamaños de muestra en un bosque natural. Puerto Almendra, Loreto, Perú, 2021 - Diaz Córdova, Cynthia Elizabeth (2022)
The study was carried out in the Arboretum “El Huayo” - CIEFOR Puerto Almendra - FCF - UNAP, San Juan Bautista district, Maynas province, Loreto region. The objective was to know the diameter - total height association in trees of the species Iryanthera juruensis Warb. "Cumala colorada" and Guarea macrophylla M. Vahl "requia blanca" in different samples. As data, the diameter (dbh) and total height of the trees of the two forest species with dbh ? 10 cm were considered. The results indicate that in the diameter - total height association in the Iryanthera juruensis Warb. "cumala colorada" plants, 2 allometric models of greater adjustment were defined; cubic and S - curve; An excellent association was also determined between the variables evaluated. For the species Guarea macrophylla M. Vahl “requia blanca” was defined with a better fit to the cubic allometric model and the association between the variables was between fair and excellent.